Stick-Slip Friction of PDMS Surfaces for Bioinspired Adhesives - Xue, Longjian (Langmuir : the ACS journal of surfaces and colloids, 2016)
Friction plays an important role in the adhesion of many climbing organisms, such as the gecko. During the shearing between two surfaces, periodic stick-slip behavior is often observed and may be critical to the adhesion of gecko setae and gecko-inspired adhesives. Here, we investigate the influence of short oligomers and pendent chains on the stick-slip friction of polydimethylsiloxane (PDMS), a commonly used material for bioinspired adhesives. Three different stick-slip patterns were observed on these surfaces (flat or microstructured) depending on the presence or absence of oligomers and their ability to diffuse out of the material. After washing samples to remove any untethered oligomeric chains, or after oxygen plasma treatment to convert the surface to a thin layer of silica, we decouple the contributions of stiffness, oligomers, and pendant chains to the stick-slip behavior. The stick phase is mainly controlled by the stiffness while the amount of untethered oligomers and pendant chains available at the contact interface defines the slip phase. A large amount of oligomers and pendant chains resulted in a large slip time, dominating the period of stick-slip motion